ALLEGORY AND APPLICABILITY: THE INTERSECTION BETWEEN THE REAL AND THE FANTASTIC IN THE HOBBITS - Turino, Isabela Delli Colli Zocolaro [UNESP]; Souza, Renata Junqueira de [UNESP] (Univ Federal Juiz Fora, Campus Univ, 2023)
Considering the growing interest in fantastic stories, we seek, in this article, to analyze Tolkien's fantastic characters, the hobbits, and understand whether such fantasy stories, although surrounded by the supernatural, bring elements that help the reader to reflect on the prosaic world where they live. To this end, we investigated this theme based on authors such as Tolkien (2006) and Held (1980), who helped us to establish possible connections between the fantastic and the real.
Keywords: Fantastic Literature. J. R. R. Tolkien. The hobbit